2021
DOI: 10.1002/star.202100139
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Rice and Wheat Based Snacks with Modulated Starch Digestibility by Altering the Dietary Composition

Abstract: Diabetes and other metabolic disorders are increasing at an alarming rate worldwide. This study aims to formulate rice-based and wheat-based snack khakhra, a pan-baked snack, with macronutrient distribution for diabetics, as per the guidelines issued by the American Diabetes Association. Protein, fiber, and fat-rich ingredients are used to modulate the starch hydrolysis pattern with 50-52%, 28-32%, and 16-20% of energy from carbohydrate, fat, and protein, respectively. It is observed that upon nutrient enrichm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…However, recent reports by Bhat et al. [ 54 ] revealed that the mixture of different starchy flour such as rice‐chickpea and wheat‐chickpea to prepare khakhra (pan‐baked snack) showed reduced predicted GI and GL compared to the khakhra prepared from the rice/wheat flour alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent reports by Bhat et al. [ 54 ] revealed that the mixture of different starchy flour such as rice‐chickpea and wheat‐chickpea to prepare khakhra (pan‐baked snack) showed reduced predicted GI and GL compared to the khakhra prepared from the rice/wheat flour alone.…”
Section: Resultsmentioning
confidence: 99%
“…The reports covering various food combinations followed by cooling on the GL of starchy foods are elusive. However, recent reports by Bhat et al [54] revealed that the mixture of different starchy S5, Supporting Information).…”
Section: Effect Of Pulse-potato Combinations and Cooling On The Estim...mentioning
confidence: 97%
“…It is a vital commodity that supports nearly a billion households across 115 countries in Asia, Africa, and America, providing a source of livelihood for millions of people (Sharif et al 2013). Rice is a versatile ingredient that plays a significant role in various cuisines, including breakfast cereals, staple carbohydrates, snacks, alcoholic beverages, and desserts (Ghosh et al 2014;Ray et al 2016;Nath et al 2019;Bhatt et al 2022;Parthasarathi et al 2022). As a staple food, rice is crucial in the fight against world hunger and poverty.…”
Section: Introductionmentioning
confidence: 99%